Transient Global Amnesia: An Electrophysiological Disorder Based on Cortical Spreading Depression—Transient Global Amnesia Model - Ding, Xuejiao; Peng, Dantao (Frontiers in Human Neuroscience, 2020)
Transient global amnesia (TGA) is a benign memory disorder with etiologies under long-term debate. The prevalence of stressful events before TGA attack make these precipitating factors not to be easily overlooked, given stress has the potential to make organic effect on the brain. Cortical spreading depression (CSD) has been proposed as a possible cause decades ago. Being a regional phenomenon, CSD seems to affect every aspect of micro-mechanism in maintaining the homeostasis of the central nervous system (CNS). Corresponding evidences regarding hemodynamic and morphological changes from TGA and CSD have been accumulated separately, but the resemblance between the two has not be systematically explored so far, especially considering CSD had been confirmed to cause secondary damage in the human brain. Thus, by delving deep into the anatomic and electrophysiological properties of the CNS, CSD-TGA model may render insights into the basic pathophysiology behind the façade of the enigmatic clinical presentation.